The C-terminal domains of ADA2 proteins determine selective incorporation into GCN5-containing complexes that target histone H3 or H4 for acetylation. - Vamos, E.E.; Boros, I.M. (FEBS Letters, 2012)
ADA2 adaptor proteins are essential subunits of GCN5-containing histone acetyltransferase (HAT) complexes. In metazoa ADA2a is present in the histone H4-specific ATAC, and ADA2b in the histone H3-specific SAGA complex. Using domain-swapped ADA2 chimeras, we determined that the in vivo function of Drosophila melanogaster SAGA and ATAC HAT complexes depend on the C-terminal region of the ADA2 subunit they contain. Our findings demonstrate that the ADA2 C-terminal regions play an important role in the specific incorporation of ADA2 into SAGA- or ATAC-type complexes, which in turn determines H3- or H4-specific histone targeting.